GIS and spatial analysis in veterinary - Durr, P. A. (CABI Publishing, 2004)
GIS and spatial analysis in veterinary, topics covered include the application of GIS to epidemic disease response, to companion animal epidemiology and to the management of wildife diseases. It also covers issues such as parallels with human health and spatial statistics in the biomedical sciences. The book will be of significant interest to researchers in veterinary epidemiology and geography.